THE VALUE OF STATISTICAL LIFE IN THE CZECH LABOR MARKET - Albrechtová, Aneta; Dušek, Libor; Janíčko, Martin, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This thesis calculates the value of statistical life (VSL) in the Czech Republic based on estimation of fatal risk computed across occupation within industries. Using the regression analysis, I estimate the impact of the fatal risk on wage. From this I calculate the VSL using the hedonic wage model. I use randomized wage data sample with 150 000 observations from the year 2013 combined with injury data from the years 2013-2015. Based on this data I estimated the VSL to be in a range between 6 965 277CZK (260 092EURO) and 37 355 674CZK (1. 394mil.EURO) based on statistically significant estimates of fatal risk. Furthermore, I estimate my model of fatal risk calculated across industries to compare the impact of the level of risk in the computation. This regression indicates that estimates based on risk in industries are overestimated. My results show that the method of risk computation is a key factor affecting the VSL.
Vedoucí práce: Libor Dušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses